Evaluation of stress among postgraduate clinical residence in Faculty of Dentistry, Universiti Teknologi MARA (UiTM), Malaysia: a pilot study / Anis Maizan Azmimurad … [et al.] - Azmimurad, Anis Maizan; Md Amin, Masturina; Abdul Halim, Rohaida; Noor, Erni (2019)
To identify the perceived stressor among dental postgraduate clinical residents in Faculty of Dentistry, Universiti Teknologi MARA (UiTM). Materials and methods: Thirty-one postgraduate clinical residents (PG) were invited to participate in the study via online survey. Among the 31, only 25 (80.7%) responded to the questionnaires. Result: Majority of the respondent (80%) were females and the mean age was 31 (SD=62.64). The result showed that 53.3% of the PG reported they were stressed, with female (87.5%) being more stressed than males but this was statistically non-significant. Main contributor for elevated stress levels were (i) lack of time for relaxation and neglect of personal life (86.7%), (ii) too much workload inadequate time (93.3%), and (iii) stress of academic activities like seminar and case presentation (100%). Hanging out with friends (83.3%) and music (76.7%) were found to be the most preferred option of PG to cope with stress. Conclusion: The current study found PG clinical residents in Faculty of Dentistry, UiTM have high level of stress. The findings of this study further support the need to consider re-evaluation and improvement of the curriculum design in order to minimize students’ stress level.